Application of chemical dyes as colour indicator for selective isolation of acetic acid bacteria - Duthathai Fujaroen (2018)
Thermotolerant acetic acid bacteria were isolated from 15 kinds of flower namely Allamanda cathartica L., Antigonon leptopus Hook.t Arn., Bidens bipinnaata L., Brunfelsia hopeana Benth., Cassia surattensis Burm.f., Ervatamia divaricata, Euphorbia milii Desmoul., Ixora lobbii Loud., Jasminum multiflorum, Lantana trifolia L., Lonicera japonica Thun., Nerin indicum Mill., Petrea volubilis L., Plumeria acutifolia and Zinnia angustifolia Kunth. using potato medium supplemented with 4% ethanol (v/v) as an enrichment medium. Three different dyes namely 0.0016% bromocresol green, 0.0016% bromocresol purple and 0.0016% bromophenol blue were also incorporated in the enrichment broth for comparison. The numbers of successful isolation obtained from each dye were nearly the same and there were no significant differences between the dyes tested (α>0.05). However, the use of 0.0016% bromocresol purple as indicator for the isolation of thermotolerant acetic acid bacteria from flowers was recommended due to its most easily observed colour change. Morphological and biochemical determinations indicated that most of thermotolerant isolates obtained were members of the genus Gluconobacter. © 2007 Academic Journals Inc.